Development and large-scale production of human milk fat analog by fermentation of microalgae - Zhou, Xiaoying; Zhao, Xinhua; Parker, Leon; Derkach, Paul; Correa, Mona; Benites, Veronica; Miller, Roberta; Athanasiadis, Dino; Doherty, Bryce; Alnozaili, Gawharah; Wittenberg, Jon; Gates, Daniel; et al. (Frontiers in Nutrition, 2024)
Background: Human milk contains a complex mixture of triacylglycerols (TAG), making it challenging to recreate using common ingredients.Objective: The study aimed to develop an innovative fermentation technique to produce essential human milk TAG, tackling a significant hurdle in infant nutrition. Method: In-depth analysis of the literature has been conducted to identify the specific TAG to be targeted. We used a microalgal oil production platform and a two-step procedure to modify its fatty acid and TAG composition. The palmitic acid (16:0) content has been increased by classical strain improvement techniques, followed by a step involving the expression of a lysophosphatidic acid acyltransferase (LPAAT) sequence capable of esterifying 16:0 specifically at the internal position (sn-2 palmitate) of TAG. Once the strain was stabilized, the fermentation was scaled up in a 50 L reactor to yield several kilograms of biomass. Subsequently, the oil was extracted and refined using standard oil processing conditions. Liquid chromatography, Mass-spectrometry was employed to monitor the TAG profile and the regiospecificity of 16:0 at the internal position (sn-2 palmitate) of TAG.The initial strain had a 16:0 level of 25% of total fatty acids, which was increased to 30% by classical strain improvement. Simultaneously, the oleic acid level decreased from 61% to 57% of total fatty acids. Upon expression of an exogenous LPAAT gene, the level of the 16:0 esterified in the internal position of the TAG (sn-2 palmitate) increased by a factor of 10, from 6 to 69% of total fatty acids. Consequently, the concentration of oleic acid in the internal position decreased from 81% to 22% of total fatty acids, with TAG analysis confirming that the primary TAG species in the oil was 1,3-dioleoyl-2-palmitoyl-glycerol (OPO). The 50L-scale fermentation trial confirmed the strain's ability to produce oil with a yield of >150 g of oil per liter of fermentation broth in a timeframe of 5 days, rendering the process scalable for larger-scale industrialization. Conclusions: We have demonstrated the feasibility of producing a suitable TAG composition which can be effectively integrated into the formulations of infant nutrition in combination with other fats and oils to meet the infant feeding requirements.